THE REALITY OF ARABIC LEARNING AT THE SMA/SMK AND PONDOK PESANTREN LEVEL: IMPLICATIONS ON ARABIC LANGUAGE EDUCATION IN THE ERA OF COVID-19 - Mohammad Jailani; Yoyo Yoyo; Djamaludin Perawironegoro (International Conference on Social and Islamic Studies, 2021)
The development of Arabic knowledge and information technology, so that teachers are required to improve their teaching skills in schools and Islamic boarding schools. In the concept of knowledge management, it is explained that one of the abilities that teachers must have in teaching is the ability to improve student learning outcomes. This study aims to develop a comparative analysis between modern-based learning and classical-based learning (salafiyah), to improve the study of nahwu, shorof, and darsul lughoh Arabic studies in schools and Islamic boarding schools. The research approach used in this study is a qualitative and quantitative approach or called R & D (Research and Development). The research subjects are ustadz, teachers, students, and santri. Determination of research subjects was carried out by purposive sampling, observation, and documentation techniques. The validity of this research data using triangulation. Data analysis used the Miles and Huberman model, namely data reduction, data display, and conclusion drawing/verification data. The results of the study prove that learning and teaching in the 4.0 revolution period encouraged formal and non-formal educational institutions to improve the competence of teachers or ustadz. Modern-based learning and conventional-based learning (salafiyah) are important to be creative and innovative in conveying material to students or santri. In analyzing the needs of modern and classical-based learning development, data or inputs are obtained from teachers and clerics. From the analysis of the potential and problems owned by the santri or students, they support the development of modern and classical-based learning. 20 informants chose modern and classical-based learning. The focus is on the development of modern-based learning research, to support the grammatical improvement of Arabic in Islamic boarding schools, as for the mastery of mufrodat and muhadasah in formal schools.